CIRC Learning Model Assisted-Picture Media on Writing Skills of Grade IV Students' Descriptive Text - Deva Bella Widya Fransisca; Ira Eko Retnosari (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2025)
Students’ limited understanding and skills in writing descriptive texts remain a concern that demands teachers’ attention. Many students struggle to construct their own sentences clearly and fail to summarize what they comprehend. This issue is often rooted in the use of ineffective learning models, which may hinder students from being adequately supported throughout the learning process, ultimately leading to suboptimal outcomes. This study aimed to examine the effect of the CIRC (Cooperative Integrated Reading and Composition) learning model, supported by image media, on the descriptive writing abilities of fourth-grade students at SDN Dukuh Menanggal 01/424 Surabaya. Employing a quantitative approach, the research used a quasi-experimental method with a non-equivalent pretest-posttest control group design. The population consisted of fourth-grade students, with classes IV-A and IV-B selected as the research samples. Data were gathered through a two-stage testing method—pretest and posttest—and analyzed using a t-test. The results revealed a significance value of 0.002 < 0.05, indicating a significant impact of the CIRC model assisted by images on students’ descriptive writing skills. Furthermore, the experimental class showed an increase in average scores from 67.32 (pretest) to 78 (posttest), reflecting a 10.68-point improvement in learning outcomes.